2023
DOI: 10.1126/sciimmunol.ade0958
|View full text |Cite
|
Sign up to set email alerts
|

Human neutralizing antibodies to cold linear epitopes and subdomain 1 of the SARS-CoV-2 spike glycoprotein

Abstract: Emergence of SARS-CoV-2 variants diminishes the efficacy of vaccines and antiviral monoclonal antibodies. Continued development of immunotherapies and vaccine immunogens resilient to viral evolution is therefore necessary. Using coldspot-guided antibody discovery, a screening approach that focuses on portions of the virus spike glycoprotein that are both functionally relevant and averse to change, we identified human neutralizing antibodies to highly conserved viral epitopes. Antibody fp.006 binds the fusion p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
73
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(77 citation statements)
references
References 71 publications
4
73
0
Order By: Relevance
“…More recently, a FP-targeted nAb, fp.006, isolated from COVID-19 convalescents, binds to a core epitope (S 813 RRSFIEDLLFNK 825 ) containing the S2ʹ site and the helical FP segment. 54 Structural analysis further revealed that R815, E819 and F823 are the key residues recognized by fp.006, which is similar to FP-targeted nAbs (e.g., COV44-79 and COV44-79). The epitope peptide bound to fp.006 is folded as an amphipathic α-helix in the Fab groove.…”
Section: Broad-spectrum Therapeutic Nabs Targeting the S2 Fusion Subunitmentioning
confidence: 78%
See 2 more Smart Citations
“…More recently, a FP-targeted nAb, fp.006, isolated from COVID-19 convalescents, binds to a core epitope (S 813 RRSFIEDLLFNK 825 ) containing the S2ʹ site and the helical FP segment. 54 Structural analysis further revealed that R815, E819 and F823 are the key residues recognized by fp.006, which is similar to FP-targeted nAbs (e.g., COV44-79 and COV44-79). The epitope peptide bound to fp.006 is folded as an amphipathic α-helix in the Fab groove.…”
Section: Broad-spectrum Therapeutic Nabs Targeting the S2 Fusion Subunitmentioning
confidence: 78%
“…4a, b ). 51 54 The representative broad-spectrum nAbs targeting fusion peptide are summarized in Table 1 .…”
Section: Broad-spectrum Therapeutic Nabs Targeting the S2 Fusion Subunitmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, of the five peptides showing boosted responses, two overlapped the N- and C- termini of the receptor-binding domain (RBD), while the remaining three boosted epitopes were all located outside the RBD region, but their recognition strongly correlated with NT 50 . Consistent with the apparent importance of these non-canonical/non-RBD responses, a recent study described highly conserved coldspots across the S protein that are maintained in all SARS-CoV-2 variants that elicited neutralizing antibodies to five epitopes that overlap with the VirScan-defined vaccine-boosted epitopes (P1–P4) [ 48 ]. The exception was an epitope [aa 812–868] near the fusion peptide in the S2 subunit that did not show a stepwise increase in magnitude across post-vaccination timepoints.…”
Section: Discussionmentioning
confidence: 89%
“…Second, there is concern over pseudotype assays that, for the convenience of scale and automation, are used as surrogates for the neutralization of SARS-CoV-2, as the distributions of S trimers on VSV and authentic SARS-CoV-2 are very different, as mentioned above [ 14 , 15 ]. The S protein-VSV pseudotype was variously shown to give neutralization that was statistically close to the neutralization of an infectious SARS-CoV-2 laboratory-adapted virus of that time [ 34 ] or was 21-fold more sensitive [ 22 ].…”
Section: What Can the Sars-cov-2 Field Learn From Hiv-1?mentioning
confidence: 99%